Synthesis, anti-inflammatory and molecular docking of some new 1,2,4-triazolobenzimidazol-3-yl acetone thiosemicarbazone cyclized derivatives as PLA-2 inhibitors - Abdelmoty, Samia G. (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The present work is carried out for the synthesis and evaluation of some new 1,3,4-thiadiazolines, 1,3-thiazolines and 1,3-thiazolidin-4-ones linked to 1,2,4-triazolo[1,5-a]benzimidazole as anti-inflammatory agents. Structure elucidation of these compounds was confirmed by IR, 1H-NMR, and mass spectrometry along with elemental microanalyses. All new compounds were tested for their anti-inflammatory activity in comparison to indomethacin (INM) where some of them showed promising results comparable to INM at 4 hours interval. The most active anti-inflammatory compounds (4b, 8c and 9a) were examined on gastric mucosa and didn’t show any gastric ulcerogenic effect compared with the reference INM. Moreover, LD50 of compounds (4b and 9a) were determined in mice; they were found non toxic up to 400 mg Kg–1 (i.p.). Also, docking simulation of some compounds into PLA2 active sites was studied.